2022
DOI: 10.3389/fnins.2022.972870
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex neural activity predicts reduction of non-suicidal self-injury in adolescents with major depressive disorder: An event related potential study

Abstract: BackgroundNon-suicidal self-injury (NSSI) is common in adolescent MDD, which is also a risk factor for suicide. However, there is few research on biomarkers and predictors about treatment response of NSSI. The purpose of this study was to find the difference of P300 between adolescent MDD with NSSI and healthy controls, and to explore whether the baseline electrophysiological level can predict the change of NSSI after treatment.MethodsWe collected 62 first-episode drug-naïve MDD adolescents with NSSI (MDD with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Activity dependent changes in myelin, including regulation of oligodendrocytes by BDNF and neurotransmitters, has also been described ( Monje, 2018 ; Xin and Chan, 2020 ). Increased myelination in the prefrontal cortex correlates with depression ( Liu et al, 2022 ). Most notably, a recent study in humans and animals found that increased myelin in the amygdala was associated with PTSD susceptibility and correlated with fear conditioning in animals ( Long et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activity dependent changes in myelin, including regulation of oligodendrocytes by BDNF and neurotransmitters, has also been described ( Monje, 2018 ; Xin and Chan, 2020 ). Increased myelination in the prefrontal cortex correlates with depression ( Liu et al, 2022 ). Most notably, a recent study in humans and animals found that increased myelin in the amygdala was associated with PTSD susceptibility and correlated with fear conditioning in animals ( Long et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in investigating the pathogenesis of adolescent depression using functional magnetic resonance imaging (fMRI). Previous studies showed that the prefrontal cortex may play a crucial role in regulating emotional responses ( 7 ), and abnormal functional connectivity (FC) in this brain region may be closely related to NSSI behavior ( 8 ). However, limited research has been conducted on the correlation between altered FC in the prefrontal cortex and NSSI among adolescents with depression.…”
Section: Introductionmentioning
confidence: 99%